PERBAIKAN PROSES PRODUKSI IKM XYZ BERDASARKAN KRITERIA CPPB-IRT, WISE, DAN SJH LPPOM MUI - Suhardi, Bambang; Wardani, Serlita Vidinia; Jauhari, Wakhid Ahmad (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2019)
Keamanan pangan merupakan hal penting yang perlu diperhatikan dalam maraknya perkembangan industri pangan di Indonesia. UU RI No. 12 Tahun 2012 mengamanatkan bahwa keamanan pangan dapat dijaga dengan memperhatikan program higiene dan sanitasi produksi serta perancangan sistem kerja dan K3 suatu industri. Keamanan pangan identik dengan kehalalan pangan karena kaidah halal adalah menjaga pangan dari kemungkinan cemaran yang membahayakan. Kewajiban bagi setiap produk yang masuk, beredar, dan diperdagangkan di wilayah Indonesia untuk bersertifikat halal tercantum pada pasal 4 Undang-Undang No. 33 Tahun 2014 tentang Jaminan Produk Halal (UU JPH). Penelitian ini bertujuan untuk mengidentifikasi kondisi keamanan dan kehalalan pangan pada proses produksi Industri Kecil Menengah (IKM) XYZ berdasarkan standar Cara Pengolahan Pangan yang Baik Industri Rumah Tangga (CPPB-IRT), Work Improvement in Small Enteprises (WISE), dan Sertifikasi Jaminan Halal (SJH) LPPOM MUI. Berdasarkan hasil identifikasi, diketahui bahwa terdapat 18 ketidaksesuaian CPPB-IRT, 10 ketidaksesuaian WISE, dan 9 ketidaksesuaian SJH LPPOM MUI pada proses produksi IKM XYZ. Berdasarkan diskusi yang telah dilakukan, disimpulkan bahwa ketidaksesuaian yang menjadi fokus perbaikan dapat dikelompokan dalam 1 kategori utama, yaitu kategori Program Higiene dan Sanitasi IKM sehingga usulan perbaikan yang tepat diimplementasikan adalah penyusunan dokumen Sanitation Standard Operating Procedures (SSOP).Â Abstract[Improvement of IKM XYZ Production Process Based on the Regulations of CPPB-IRT, WISE, and SJH LPPOM MUI] Food Safety is an important thing to note in the middle of the development of the food industry in Indonesia. UU RI Number 12 of 2012 mandates that food safety can be maintained by paying attention to hygiene and sanitation programs, work system design, and also occupational safety and health in the production process of an industry. The thing that is closely related to food safety is halal practice. Halal is a guarantee of food safety because the implementation of halal means getting rid of things that are harmful to humanity and the environment. The obligation for every product that entered, circulated, and traded in Indonesian territory for halal certification are listed in Article 4 of UU RI Number 33 of 2014 concerning Guaranteed Halal Products. This study aims to identify the condition of food safety and halal practice in IKM XYZ based on the regulations of Cara Produksi Pangan yang Baik Industri Rumah Tangga (CPPB-IRT), Work Improvement in Small Enterprises (WISE), and Halal Assurance Certification of LPPOM MUI, and also to compile improvement proposal based on the identification results. The identification results show that in the IKM XYZ production process, there are 18 elements that not following CPPB-IRT regulations, 10 elements that are not following WISE regulations, and 9 elements that are not following Halal Assurance Certification of LPPOM MUI. Based on the results of discussion that have been carried out with the owner and the supervisor of IKM XYZ, elements that are being the focus of improvement can be grouped into 1 main category, that is Program Hygiene dan Sanitasi IKM. So, the improvement proposal that fits is the documentation of Sanitation Standard Operating Procedures (SSOP).Keywords: CPPB-IRT; food safety; IKM, SJH LPPOM MUI; WISE